Importance of habitat heterogeneity in tidal flats to the conservation of migratory shorebirds - Cai, Shangxiao; Mu, Tong; Peng, He‐Bo; Ma, Zhijun; Wilcove, David S. (Conservation biology, 2024)
Understanding species distribution patterns and what determines them is critical for effective conservation planning and management. In the case of shorebirds migrating along the East Asian‐Australasian Flyway (EAAF), the loss of stopover habitat in the Yellow Sea region is thought to be the primary reason for the precipitous population declines. However, the rates of decline vary considerably among species, and it remains unclear how such differences could arise within a group of closely related species using apparently similar habitats at the same locales. We mapped the spatial distributions of foraging shorebirds, as well as biotic (benthic invertebrates consumed by migrating shorebirds) and abiotic (sediment characteristics) environmental factors, at a key stopover site in eastern China. Five of the six sediment characteristics showed significant spatial variation with respect to distance along the shoreline or distance from the seawall in the same tidal flat. The biomasses of four of the six most abundant benthic invertebrates were concentrated in the upper or middle zones of the tidal flat. The distribution patterns of all three focal shorebird species on the tidal flat were best explained jointly by this heterogeneity of sediment characteristics and invertebrate prey. These results suggest that the loss of tidal flats along the Yellow Sea, which is typically concentrated at the upper and middle zones, may not only reduce the overall amount of staging habitat, but also disproportionately affect the most resource‐rich portions for the birds. Effective conservation of shorebird staging areas along the EAAF and likely elsewhere must consider the subtle habitat heterogeneity that characterizes these tidal flats, prioritizing the protection of those portions richest in food resources, most frequently used by focal bird species, and most vulnerable to anthropogenic threats. Article impact statement: Heterogeneity of tidal flats with respect to biotic and abiotic factors must be considered in shorebird conservation planning. Importancia de la heterogeneidad de hábitat en las llanuras intermareales para la conservación de aves playeras migratorias Resumen Entender las pautas de distribución de las especies y los factores que las determinan es fundamental para planificar y gestionar eficazmente su conservación. En el caso de las aves playeras que migran a lo largo de la ruta migratoria Asia Oriental‐Australasia (EAAF, en inglés), se cree que la pérdida de puntos de parada en la región del Mar Amarillo es la razón principal de la declinación poblacional precipitada. Sin embargo, las tasas de declinación varían considerablemente entre especies, y sigue sin estar claro cómo pueden surgir tales diferencias dentro de un grupo de especies emparentadas que utilizan hábitats aparentemente similares en los mismos lugares. Mapeamos las distribuciones espaciales de las aves playeras forrajeras, así como los factores ambientales bióticos (invertebrados bénticos consumidos por las aves playeras migratorias) y abióticos (características de los sedimentos), en un punto de parada clave en el este de China. Cinco de las seis características de los sedimentos mostraron una variación espacial significativa con respecto a los cambios lineales en la distancia a lo largo de la costa o la distancia desde el malecón en la misma llanura mareal. La biomasa de cuatro de los seis invertebrados bénticos más abundantes se concentró en las zonas superior o media de la llanura mareal. Esta heterogeneidad de las características de los sedimentos y de las presas invertebradas es la que mejor explica los patrones de distribución de las tres especies de aves playeras en la llanura mareal. Estos resultados sugieren que la pérdida de llanuras mareales a lo largo del Mar Amarillo, que suele concentrarse en las zonas superior y media, puede no sólo reducir la cantidad total de hábitat de parada, sino también afectar de manera desproporcionada a las partes más ricas en recursos para las aves. La conservación eficaz de los puntos de parada de las aves playeras a lo largo del EAAF, y probablemente en otros lugares, debe tener en cuenta la sutil heterogeneidad del hábitat que caracteriza a estas llanuras mareales, priorizando la protección de las partes más ricas en recursos alimenticios, más frecuentemente utilizadas por las especies de aves focales y más vulnerables a las amenazas antropogénicas. 潮间带滩涂异质性在迁徙鸻鹬类保护中的重要意义 【摘要】了解物种的分布格局及其决定因素, 对于制定有效的栖息地保护和管理规划至关重要。在东亚‐澳大利西亚迁飞区, 迁徙鸻鹬类的种群数量正在快速下降, 其主要原因是作为鸻鹬类迁徙停歇地的黄渤海地区潮间带滩涂面积大幅减少。然而, 尽管许多迁徙鸻鹬类亲缘关系密切, 并且都利用潮间带滩涂(甚至是同一片滩涂), 但是它们的种群数量下降速率却存在巨大差异, 而导致这种差异的原因仍然缺乏了解。在这项研究中, 我们在渤海沿岸一个重要的鸻鹬类迁徙停歇地进行了调查和取样, 分析了鸻鹬类以及相关的生物因子(鸻鹬类的食物, 即底栖无脊椎动物)和非生物环境因子(沉积物特征)在潮间带滩涂上的空间分布格局。研究发现, 在六种沉积物组分特征中, 其中五种都在垂直或平行于海岸线的方向上呈现出显著变化。在潮间带滩涂上数量最多的六种底栖无脊椎动物中, 其中四种的生物量主要分布于高潮滩或中潮滩。沉积物特征以及底栖无脊椎动物的异质性分布共同解释了三种目标鸻鹬类在潮间带滩涂上的分布格局。这些研究结果表明, 黄渤海区域潮间带滩涂栖息地的丧失, 尤其是高潮滩和中潮滩面积的急剧减少, 不仅会造成迁徙停歇地的面积下降, 更会极大地影响鸻鹬类所依赖的资源最丰富的栖息地斑块。因此, 为了更有效地保护东亚‐澳大利西亚迁飞区和其他迁飞区的鸻鹬类迁徙停歇地, 保护实践中必须将潮间带滩涂栖息地普遍存在的异质性特征考虑在内, 优先保护潮间带滩涂中食物资源最丰富, 鸟类利用最频繁, 以及受人类活动威胁最严重的斑块。